Croatia's religious story : the coexistence of institutionalized and individualized religiosity - Nikodem, Krunoslav (Array, 2012)
The main topic of this chapter is an analysis of religious changes in contemporary Croatian society. Our general hypothesis is that there are two main processes that marked religious change at the same time: stability of institutionalized (church-related) religiosity, with some indicators of slight increase, and the firm presence of individualized, personally shaped religiosity. We are analyzing those simultaneous processes in the context of religiosity (in general meaning), personal relation to religion and public role of religion. The paper is mostly based on the results of the international empirical research «Church and Religion in an Enlarged Europe» conducted in 2006 on the representative sample of 968 adult Croatian citizens (48.5% male and 51.5% female). These results are compared with the results from other international researches, such as, «Aufbruch» (N=1032 ; 1997) and the “European Value Study” (N=1003 ; 1999 ; N=1525 ; 2008), as well as the national one, «Modernization and Identity in Croatian Society» (N=1202 ; 2004).